2018
DOI: 10.1128/jcm.00018-18
|View full text |Cite
|
Sign up to set email alerts
|

Point-Counterpoint: Meningitis/Encephalitis Syndromic Testing in the Clinical Laboratory

Abstract: INTRODUCTIONSyndromic panels were first FDA cleared for detection of respiratory pathogens in 2008. Since then, other panels have been approved by the FDA, and most recently, the FilmArray meningitis/encephalitis panel (BioFire, Salt Lake City, UT) has become available. This assay detects 14 targets within 1 h and includes pathogens that typically cause different manifestations of infection, although they infect the same organ system. Several studies have reported both false-positive and false-negative results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 32 publications
2
15
0
1
Order By: Relevance
“…As the most appropriate patient population for testing with the FA-M/E panel is a point that still requires consideration [10,38], we also discussed the strategy for use of the panel in our laboratory. We found that diagnostic yield in patients hospitalized in units other than those selected for systematic FA-M/E testing were rare, suggesting that use of the panel should be restricted to patients with a high suspicion of M/E in these units to limit unnecessary tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the most appropriate patient population for testing with the FA-M/E panel is a point that still requires consideration [10,38], we also discussed the strategy for use of the panel in our laboratory. We found that diagnostic yield in patients hospitalized in units other than those selected for systematic FA-M/E testing were rare, suggesting that use of the panel should be restricted to patients with a high suspicion of M/E in these units to limit unnecessary tests.…”
Section: Discussionmentioning
confidence: 99%
“…Despite certain pitfalls identified, the authors concluded that the FA-M/E panel was a sensitive and specific test to aid in diagnosis of M/E. However, certain aspects regarding the use of the panel are still a matter of debate as illustrated by a recent point/counterpoint, underlining that prospective studies are still required and that the most appropriate patient population for testing with the FA-M/E panel has yet to be defined [10].…”
Section: Introductionmentioning
confidence: 99%
“…One of the major concerns regarding widespread use of the FA-ME panel has revolved around the relevance of HHV-6 detection and its effects on antimicrobial management (24,25). As the majority of primary HHV-6 infections in immunocompetent hosts are self-limiting, and unnecessary exposure to ganciclovir and foscarnet can lead to bone marrow suppression and renal insufficiency (26), routine antiviral therapy is not recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, two studies reported the highest proportion of false positive results to S. pneumoniae ( 17.5 and 80%) 13 , 21 , and in the present study, there were 16 detections of S. pneumoniae , of which six were negative in cultures, and clinical correlations showed that only four of them had a high level of bacterial meningitis suspicion. A positive result should be analyzed carefully and correlated with the medical chart data; repeating the test may be helpful, but a repeated negative result may not necessarily rule out an initial positive result in cases of low pathogen loads 33 , 34 other panels have been approved by the FDA, and most recently, the FilmArray meningitis/encephalitis panel (BioFire, Salt Lake City, UT.…”
Section: Discussionmentioning
confidence: 99%